Praktik Jual Beli Pre Order dengan Sistem Online: Practice of Pre-Order Buying and Selling with Online System - Utami, Indrianti Putri (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2022)
The practice of buying and selling online is a buying and selling transaction carried out through modern technology whose validity depends on whether or not the pillars and conditions that apply in buying and selling are fulfilled. Pre-order buying and selling transactions only have online catalogs of goods found on websites or social media. This study aims to determine the practice and implementation of buying and selling pre-orders with an online system at the Bylo.id and Gerai.aliyah online stores. And knowing the perspective of Sharia Economic Law on buying and selling pre-orders with the online system at the Bylo.id and Gerai.aliyah online stores. The method used in this research is the descriptive research method, a method that is intended to collect information about the object of research. The results of the study conclude that the practice and implementation of buying and selling pre-orders with the online system at the Bylo.id and Gerai.aliyah online stores is carried out by pre-orders or orders made through the website or chat, then both parties agree on the price, payment system, and delivery. and buying and selling preorders with the online system at the Bylo.id and Gerai.aliyah online stores have fulfilled the pillars and conditions for buying and selling istishna'. Praktik jual beli online merupakan transaksi jual beli yang dilakukan melalui teknologi modern yang keabsahannya tergantung pada terpenuhi atau tidaknya rukun dan syarat yang berlaku dalam jual beli. Transaksi jual beli pre order hanya memiliki katalog barang online yang terdapat di website atau media sosial. Penelitian ini bertujuan untuk mengetahui praktik dan implementasi jual beli pre order dengan system online di toko online Bylo.id dan Gerai.aliyah. Dan mengetahui perspektif Hukum Ekonomi Syariah terhadap jual beli pre order dengan sistem online di toko online Bylo.id dan Gerai.aliyah. Metode yang digunakan dalam penelitian ini adalah metode penelitian deskriptif, metode yang dimaksudkan untuk mengumpulkan informasi mengenai objek penelitian. Hasil penelitian menyimpulkan bahwa praktik dan implementasi jual beli pre order dengan sistem online di toko online Bylo.id dan Gerai.aliyah dilaksanakan dengan pre order atau pesanan yang dilakukan melalui website atau chatting, lalu kedua belah pihak bersepakat atas harga, sistem pembayaran, dan pengirimannya dan jual beli pre order dengan sistem online di toko online Bylo.id dan Gerai.aliyah telah memenuhi rukun dan syarat jual beli istishna’.